Ajustes temporais de características foliares e de copa em cafeeiro (Coffea arabica L. cultivar Mundo Novo) sob exclusão parcial de chuva em Lavras, MG - Silva, Debora Valim da (2017)
Brazil is the world’s leading producer and exporter of coffee. The state of Minas Gerais, mostly the south region, is responsible for 50% of the whole national production. Almost all coffee plantations belong to species Coffea arabica. However, the Brazilian agricultural has been impacted by extreme climate conditions, being this situation a challenge for coffee production. Due its social and economic importance, monitoring the coffee crops is fundamental. The aim was to evaluate, under field conditions, the temporal dynamic of leaf and canopy adjustments and the water use efficiency of C. arabica plants under partial rain exclusion. The experiment was set in a six year old coffee plantation at Federal University of Lavras and the evaluations were assessed from December 2015 to January 2017. The experimental design was in a completely randomized blocks, composed of three hydric conditions: system with a rainfall exclusion system (SWE), system with no rainfall exclusion (SWNE), and no rainfall exclusion (NNE), with two repetitions each block. Soil matric potential, relative water content (RWC), specific leaf area (SLA), leaf index area (LAI), and NDVI were subjected to a t -test (for parametric data) or Mann-Whitney test (for non-parametric data) (P< 0,05). The leaf anatomy data were analysed by a two-way ANOVA (hydric conditions X seasons) and the averages were compared by Tukey’s test (P< 0,05). There was no significant difference for RWC and SLA among the hydric conditions, in each season. However, the treatment SWE showed a marked reduction in LAI and NDVI averages through the Fall and Winter-2016. It agrees with the reduction in the soil matric potential, in the same seasons. Although there was no difference for stomatal number and density during the winter, plants grew under SWE conditions showed an increase in the cuticle thickness, besides a reduction in palisade parenchyma thickness. SWE in winter obtained the highest stomatal index and the largest polar diameter was found in spring in SWNE. Thus, under rain exclusion conditions mostly of the changes are relative to canopy modifications as observed for LAI and NDVI. Furthermore, the results support that coffee leaves modifies their structural anatomy in relation to the different hydric conditions.